The Role of Innovation Capacity in Improving Company Performance in Creative Industry Sub-Sector Leather Industry - Riyandi Nur Sumawidjaja; Gurawan Dayona; Yoyo Sudaryo (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2022)
This study aims to empirically examine the role of innovation capacity in improving the company's performance. The study used a quantitative explanatory survey method. Collecting data using a questionnaire with a random sampling technique. Respondents are the creative industries of the leather, leather goods, and footwear sub-sector with a sample of 252 MSMEs in the leather, leather goods, and footwear industry in West Java. The data that has been collected was analyzed using the Structural Equation Model (SEM). The results of the study show that innovation capacity significantly plays a role in improving company performance The highest contribution of each dimension of innovation capacity came from investment in research and development and the lowest was contributed by new distribution channels. Meanwhile, the highest achievement of the company's performance came from the growth and learning perspective and the lowest was contributed by the customer perspective The results of the hypothesis test show a positive and significant effect that the role innovation capacity affects in improving a company's performance is empirically acceptable.